Bajki na dobranoc - Vandewiele, Agnes; King, Dawn.; Hofer, Anne. ([Lublin : Wydawnictwo Pawel Skokowski], 1993)
World famous fairy tales adapted for young children. For ages 3-7.
Wilk i siedem kozkatek -- Trzy male swinki -- Brzydkie kaczatko -- Zlotowlosa i trzy niedzwiadki -- Calineczka -- Jas i Fasola.
Cover title.
Keywords: Fairy tales